Risk Factors of Falling in Patients with Type 2 Diabetes Mellitus - Sari, Dwi Rosella Komala; Pratiwi, Rossy Eka; Safitri, Weni; Hifayati, Laily Maulida Nur (Annual Physiotherapy Scientific Meeting Proceeding, 2022)
Background: type 2 diabetes mellitus (T2DM) is characterized by hyperglycemia. Prolonged hyperglycemia is noted impacting microvascular and macrovascular complications. Diabetic peripheral neuropathy (DPN) is the highest microvascular complication in T2DM, increasing the risk of falling. Factors of duration of DM and balance have a strong influence on the risk of falling. However, the risk factors for falls in T2DM have not been established recently. Purpose: the purpose of this study was to determine the correlation between glycemic level, DPN and postural balance in patients with T2DM, as well as to determine the dominant factor of high risk of falling in patients with T2DM. Methods: The participant in this study confirmed having T2DM by medical diagnosis for 5 years and more. The glycemic level (FGL) was measured by fasting for 8 hours glycemic level, DPN was clarified by physical examination of MNSI and postural balance was assessed by mCTSIB, BBS and TUG tests. The risk for falling was taken from the categorical score of The Timed Up and Go test with a cut score of >13.5 secs as a high risk of falling. This research used a cross-sectional study conducted in DM community in Surakarta, Central Java, Indonesia. Results: There was a correlation between FGL and DPN, DPN and static balance, as well static balance and dynamic balance. The logistic regression revealed duration of DM as a dominant factor of high risk to fall (OR 1.376, p-value+0.023, 95% CI=1.044 – 1.814). Conclusion: prolonged duration of DM combines with hyperglycemia status impact to DPN and reduces balance performance in patients with T2DM.